A Mediterranean Style Diet Is Favorably Associated with Concentrations of Circulating Ceramides and Ceramide Ratios in the Framingham Offspring Cohort (P18-048-19). (13th June 2019) - Walker, Maura; Xanthakis, Vanessa; Ma, Jiantao; Quatromoni, Paula A; Moore, Lynn; Ramachandran, Vasan; Jacques, Paul
Abstract: Objectives: A Mediterranean style diet may impact cardiometabolic health by modifying concentrations of circulating lipid species. Distinct circulating ceramide species are positively associated with cardiometabolic risk; whereas, ratios of very-long to long-chain ceramides demonstrate an inverse association. We evaluated the relation between consuming a Mediterranean-style diet with concentrations of three circulating ceramides and ceramide ratios. Methods: Participants of the Framingham Offspring cohort who attended exam cycle 8 ( n = 2174, mean age 67 years, 55% women) were categorized according to quartile of a Mediterranean-style diet score (MDS). The MDS consisted of 9 components (vegetables, fruits, nuts, legumes, whole grains, fish, red meat, monounsaturated to saturated fat ratio, and alcohol). For each component, scores in each exam cycle were based on sex-specific consumption quartiles. A higher score represents greater conformity, with a maximum score of 25. We determined the cumulative MDS, reflective of usual intake over 14 years (mean of exam cycles 5 and 8). Plasma ceramide concentrations (ug/mL) were assayed at exam 8 using a validated LC-MS/MS protocol. Multivariable linear regression was used to relate the MDS to circulating ceramide concentrations (C16:0, C22:0, and C24:0), and to ceramide ratios (C22:0/C16:0 and C24:0/C16:0) adjusting for age, sex, smoking status, lipid-lowering medications, total energy intake, physical activity, and BMI. Results: The median (IQR) MDS within each quartile was Q1: 7.5 (2.0), Q2: 11.0 (1.5), Q3: 13.5 (1), and Q4: 17.0 (3.0). A higher cumulative MDS was inversely associated with concentrations of the C16:0 (LS mean [95% CI] µg/mL; Q1: 0.169 [0.166, 0.172], Q4: 0.158 [0.155, 0.161]) and C22:0 (Q1: 0.628 [0.612, 0.643], Q4: 0.594 [0.579, 0.610]) ceramides (both Ptrend < 0.05, across quartiles). In contrast, a higher cumulative MDS was positively associated with the C24:0/C16:0 ratio (Q1: 13.41 [13.13, 13.70], Q4: 14.60 [14.33, 14.88]; Ptrend < 0.05). Associations between the MDS score and concentrations of the C24:0 ceramide and the C22:0/C16:0 ratio were not statistically significant. Conclusions: This cross-sectional study provides insight into how a Mediterranean style diet may favorably influence distinct ceramide species and ceramide ratios. Funding Sources: NIH Multidisciplinary Training Program in Cardiovascular Epidemiology, NIH National Heart Lung and Blood Institute (NHLBI) Framingham Heart Study, and the U.S. Department of Agriculture, Agricultural Research Service. Supporting Tables, Images and/or Graphs: